Bone marrow mesenchymal stem cell-derived exosomes improve cancer drug delivery in human cell lines and a mouse osteosarcoma model - Cai, Wenquan; He, Dawei (Frontiers in Oncology, 2024)
IntroductionOsteosarcoma is the most common primary bone tumor. Patients require chemotherapy drugs with high-targeting ability and low off-target toxicity to improve their survival. Exosomes are biological vesicles that mediate long-distance communication between cells and naturally target their source sites. Exosomes derived from bone marrow mesenchymal stem cells (BMSCs) naturally target bone tumor sites, suggesting their potential as effective anti-tumor therapy vectors. In this study, we evaluated the potential of BMSC-derived exosomes in targeting osteosarcoma and serving as a carrier for doxorubicin (DOX).MethodsWe isolated exosomes from human BMSCs and synthesized hybrid exosomes (HEs) by fusing these exosomes with liposomes. These HEs were loaded with DOX to produce a novel drug, HE/DOX.ResultsWe confirmed the successful synthesis of HE/DOX using fluorescence spectroscopy and estimated its size to be 151.1 ± 10.2 nm. HEs expressed the known exosomal proteins ALIX, CD63, and TSG101. Under acidic conditions similar to those observed in the tumor microenvironment, the drug release from HE/DOX was enhanced. In osteosarcoma cell lines and in a mouse osteosarcoma model, HE/DOX exhibited stronger tumor-inhibitory effects than free DOX.ConclusionsOur study demonstrates that BMSC-derived exosomes could effectively target osteosarcoma. Furthermore, HEs can serve as effective carriers of DOX, enabling the treatment of osteosarcoma. These findings highlight a promising direction for tumor-targeted therapy.